The Practical encyclopedia of good decorating and home improvement - Gipp, Jennifer (Australia : Thomson Course Technology, 2007)
Provides middle school teachers with the curricular framework needed to be successful. Introduces a concept, provides practice using the application, and then allow students to use the applications in a cross curricular scenario.
Chapter 1. Introduction to presentations -- Chapter 2. Additional slides -- Chapter 3. Animations -- Chapter 4. Sounds
Includes index.
Keywords: MICROSOFT POWERPOINT (COMPUTER FILE) -- STUDY AND TEACHING (MIDDLE SCHOOL)